P281 Exposure to widespread environmental endocrine disrupting chemicals and human sperm sex ratio. (1st September 2016) - Jurewicz, Joanna; Radwan, Michał; Jakubowski, Lucjusz; Wielgomas, Bartosz; Ligocka, Danuta; Brzeźnicki, Sławomir; Hanke, Wojciech
Abstract : In recent years, a trend toward a declining proportion of male births has been noted in several, but not all, industrialised countries. The underlying reason for the drop in the sex ratio is unclear, but one theory states that widespread environmental endocrine disrupting chemicals affecting the male reproductive system in a negative manner could be part of the explanation. The present study was designed to investigate whether the urinary phthalate, pyrethroids and polycyclic aromatic hydrocarbons metabolites concentrations were associated with sperm Y:X ratio. The study population consisted of 194 men aged under 45 years of age who attended infertility clinic in Lodz, Poland for diagnostic purposes with normal semen concentration of 20–300 mln/ml or with slight oligozoospermia (semen concentration of 15–20 mln/ml) (WHO, 1999). The Y:X ratio was assessed by fluorescent in situ hybridization. Urinary concentrations of 1-hydroxypyrene were measured by high performance liquid chromatography, phthalate metabolites were analysed using a procedure based on the LC-MS/MS methods and metabolites of synthetic pyrethroids were assessed by gas chromatography ion-tap mass spectrometry method. After adjustment for potential confounders (past diseases, age, abstinence, smoking, alcohol consumption, sperm concentration, motility, morphology) 5 OH MEHP, CDCCA to TDCCA and 1-OHP was negatively related to Y:X sperm chromosome ratio (p = 0.033, p < 0.001, p = 0.047 respectively). As this is the first study to elucidate the association between the level of metabolites of widespread environmental endocrine disrupting chemicals (phthalates, synthetic pyrethroids, polycyclic aromatic hydrocarbons) on sex chromosome ratio in sperm therefore, these findings require further replication in other populations.